2022
DOI: 10.3389/fpsyg.2021.824123
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness in Judokas and Team Athletes: Predictive Value of Personality Traits, Emotional Intelligence and Self-Efficacy

Abstract: Combat sports and martial arts are often associated with aggressiveness among the general public, although data on judo and/or martial arts and aggressiveness seem to be unclear. This research aims to compare athletes who have trained judo for a prolonged time (minimum 5 years) and athletes from various team sports, primarily regarding the manifestation of aggression, but also regarding personality traits, emotional intelligence, and self-efficacy. Also, the potential predictive value of personality traits, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
1
6
0
1
Order By: Relevance
“…This is consistent with data from other studies that also reported direct associations between EI and exercise [ 3 , 29 , 30 , 31 , 32 , 33 ]. It is not surprising that people who exercise have better EI because they strive to be the best and often want to lead, and EI is an important trait for leadership [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with data from other studies that also reported direct associations between EI and exercise [ 3 , 29 , 30 , 31 , 32 , 33 ]. It is not surprising that people who exercise have better EI because they strive to be the best and often want to lead, and EI is an important trait for leadership [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…One recent systematic review showed that EI is a determining factor in the improvement in sports competencies [ 31 ]. Stanković et al concluded that elite athletes are characterized by positive, high scores in self-efficacy and emotionality [ 32 ]. Ubago-Jiménez found that the relationship between PA and EI is stronger in male than in female students [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, superficial analyses of our data (not shown) discarded the association between BPQ anger and HGS. Although martial arts and combat sports are often associated with aggressiveness by the general public, there is evidence of less verbal and physical manifested aggressiveness in combat sports (i.e., Judo) practitioners in comparison with team sports [ 45 ]. Thus, based on the outcomes found here and the investigations of other researchers, it can be stated that aggressive behavior can be altered, modified, relieved, or retarded through exercise training routines.…”
Section: Discussionmentioning
confidence: 99%
“…En el ámbito deportivo, la ira tiene un papel principal tanto positivo como negativo no solo en el rendimiento, sino también en la propia elección de la actividad deportiva que se quiere realizar (Nicholls, 1989;Stankovic et al, 2022).…”
Section: Introductionunclassified